Neuromuscular ultrasound as a biomarker in the SOD1 mouse model of amyotrophic lateral sclerosis - Camilla Wohnrade; Nadine Thau-Habermann; Thomas Gschwendtberger; Julia Rückoldt; Zhong Huang; Stefanie Schreiber; Kirsten Haastert-Talini; Susanne Petri (PLoS ONE, 2026)
A progression marker that indicates early disease-related changes and treatment responses in the to date incurable neurodegenerative disease amyotrophic lateral sclerosis (ALS) is highly desirable. Translation of therapeutics that have been successful in in vivo models into trials in human patients has proven difficult in recent decades. This failure can be attributed, at least in part, to the lack of specific biomarkers for ALS diagnosis and progression in human ALS patients as well as in in vivo models. Neuromuscular ultrasound is an easily accessible, non-invasive tool to support diagnosis of ALS in humans. Our current study shows for the first time that the disease can be detected in an ALS mouse model with the help of neuromuscular ultrasound. We characterized disease progression regarding changes in the peripheral nerves and muscles of the hind limb in the SOD1 G93A mouse model of ALS using different techniques (neuromuscular ultrasound, electroneurography, motor function tests, phenotypic assessments and histology). By neuromuscular ultrasound, we measured the cross-sectional area and diameter of the sciatic nerve and analyzed hind limb muscle texture and thickness. Our results show that motor neuron loss and muscle atrophy – analogous to ALS in humans – can be measured by ultrasound in the SOD1 G93A mouse model. Changes in nerve and muscle morphology appear at the same time or even before changes in the established tests (including electroneurographic measurements) performed in vivo in this model. Correlations with histologic features of disease progression make neuromuscular ultrasound a sensitive, non-invasive outcome marker for preclinical studies.